Altered cytochrome 2E1 and 3A P450‐dependent drug metabolism in advanced ovarian cancer correlates to tumour‐associated inflammation. (5th August 2019) - Trousil, Sebastian; Lee, Patrizia; Edwards, Robert J.; Maslen, Lynn; Lozan‐Kuehne, Jingky P.; Ramaswami, Ramya; Aboagye, Eric O.; Clarke, Stephen; Liddle, Christopher; Sharma, Rohini
Abstract : Background and Purpose: Previous work has focussed on changes in drug metabolism caused by altered activity of CYP3A in the presence of inflammation and, in particular, inflammation associated with malignancy. However, drug metabolism involves a number of other P450s, and therefore, we assessed the effect of cancer‐related inflammation on multiple CYP enzymes using a validated drug cocktail. Experimental Approach: Patients with advanced stage ovarian cancer and healthy volunteers were recruited. Participants received caffeine, chlorzoxazone, dextromethorphan, and omeprazole as in vivo probes for CYP1A2, CYP2E1, CYP2D6, CYP3A, and CYP2C19. Blood was collected for serum C‐reactive protein and cytokine analysis. Key Results: CYP2E1 activity was markedly up‐regulated in cancer (6‐hydroxychlorzoxazone/chlorzoxazone ratio of 1.30 vs. 2.75), while CYP3A phenotypic activity was repressed in cancer (omeprazole sulfone/omeprazole ratio of 0.23 vs. 0.49). Increased activity of CYP2E1 was associated with raised serum levels of IL‐6, IL‐8, and TNF‐α. Repression of CYP3A correlated with raised levels of serum C‐reactive protein, IL‐6, IL‐8, and TNF‐α. Conclusions and Implications: CYP enzyme activity is differentially affected by the presence of tumour‐associated inflammation, affecting particularly CYP2E1‐ and CYP3A‐mediated drug metabolism, and may have profound implications for drug development and prescribing in oncological settings.